The impact of neuroscience on society: cognitive enhancement in neuropsychiatric disorders and in healthy people - Sahakian, Barbara J. (Philos Trans R Soc Lond B Biol Sci, 2015)
In addition to causing distress and disability to the individual, neuropsychiatric disorders are also extremely expensive to society and governments. These disorders are both common and debilitating and impact on cognition, functionality and wellbeing. Cognitive enhancing drugs, such as cholinesterase inhibitors and methylphenidate, are used to treat cognitive dysfunction in Alzheimer's disease and attention deficit hyperactivity disorder, respectively. Other cognitive enhancers include specific computerized cognitive training and devices. An example of a novel form of cognitive enhancement using the technological advancement of a game on an iPad that also acts to increase motivation is presented. Cognitive enhancing drugs, such as methylphenidate and modafinil, which were developed as treatments, are increasingly being used by healthy people. Modafinil not only affects ‘cold’ cognition, but also improves ‘hot’ cognition, such as emotion recognition and task-related motivation. The lifestyle use of ‘smart drugs' raises both safety concerns as well as ethical issues, including coercion and increasing disparity in society. As a society, we need to consider which forms of cognitive enhancement (e.g. pharmacological, exercise, lifelong learning) are acceptable and for which groups (e.g. military, doctors) under what conditions (e.g. war, shift work) and by what methods we would wish to improve and flourish.